2018
DOI: 10.1055/s-0038-1648220
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Experience in Lymphovenous Anastomosis for Lymphedema Treatment: The Learning Curve Effect on the Overall Outcome

Abstract: LVA is an effective treatment option to reduce the volume in the affected limb and to improve symptoms involved. Regardless of the number and experience of the surgeons, cellulitis improves significantly after LVA. The experience of the surgeon does not significantly impact the positive outcome while proficiency increases with experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 30 publications
1
58
0
Order By: Relevance
“…An out-to-in transluminal suture is placed through a vein with a large diameter, followed by an in-to-out transluminal suture, which intussuscepts all the lymphatic vessels into the vein, and forms an LVA complex that resembles an octopus. 50 Per case 1 29,30,36,[51][52][53] to 18 46 anastomoses were performed, and it took an average of 3 to 4 hours 29,35,[44][45][46][54][55][56][57][58] for surgeons to perform the entire procedure. Follow-up time ranged from 1 59,60 to 87 months.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An out-to-in transluminal suture is placed through a vein with a large diameter, followed by an in-to-out transluminal suture, which intussuscepts all the lymphatic vessels into the vein, and forms an LVA complex that resembles an octopus. 50 Per case 1 29,30,36,[51][52][53] to 18 46 anastomoses were performed, and it took an average of 3 to 4 hours 29,35,[44][45][46][54][55][56][57][58] for surgeons to perform the entire procedure. Follow-up time ranged from 1 59,60 to 87 months.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies assessed the relationship between lymphedema and episodes of cellulitis or lymphangitis. 1,24,27,29,30,34,38,56,60,61,[63][64][65] All, except one chart review by Lee et al, 63 reported significant reductions in infection incidence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reflecting the current trend toward perforator flap or supermicrosurgery, there has been an increase interest in ultrasound use in reconstructive microsurgery, especially in supermicrosurgery cases. [30][31][32][33][34] During 2019, there were at least three lymphedema symposiums, and one supermicrosurgery symposium. In 2020, the second Ultrasound Symposium for Reconstructive Microsurgery will be held in Rome.…”
Section: Discussionmentioning
confidence: 99%
“…However, a beginner when performing lymphovenous anastomosis supermicrosurgery may still show reasonable results as long as he or she abides by the principle of supermicrosurgery. As experience accumulates, one can expect better proficiency by decreasing anastomosis and dissection time . Special instruments, such as fine dilators, forceps, and microscissors, designed for supermicrosurgery will help to make the process smoother.…”
Section: The Principlesmentioning
confidence: 99%